Exploring Cannabidiol’s Therapeutic Role in Colorectal Cancer: Network Pharmacology and Molecular Docking Insights - Juan Manuel Guzmán-Flores; Fernando Martínez-Esquivias; Antistio Alviz-Amador; Guadalupe Thonanzyn Avilés-Rodríguez; Michel Fabricio García-Azuela (Scientia Pharmaceutica)
Background: Colorectal cancer (CRC) is one of the most prevalent cancers worldwide, and current treatments have significant side effects. Cannabidiol (CBD), a compound derived from Cannabis sativa, has demonstrated promising anticancer properties. However, further investigation is required to elucidate its underlying molecular mechanisms. Methods: Network pharmacology and molecular docking analysis approaches were utilized. Molecular targets of CBD and CRC-associated genes were identified using the Swiss Target Prediction, Malacards, and DisGeNet databases. Protein–protein interactions were analyzed using the STRING and Cytoscape. Ontology enrichment was conducted using ShinyGO, and gene expression and immune infiltration were evaluated with UALCAN and TISIDB. Results: We found 95 common genes between CRC and CBD targets. Six major genes (ANXA5, IGF1R, JAK2, MAPK8, MDM2, and PARP1) were particularly interesting due to their high connectivity and role in relevant metabolic pathways. The results of the molecular docking analysis indicated that CBD interacts favorably with these genes, modulating critical pathways such as RAS/MAPK and PI3K-AKT/FoxO, which are involved in cell proliferation, apoptosis, and cell cycle regulation. ANXA5 and JAK2 were identified as particularly relevant, as they correlated significantly with immune cell infiltration, suggesting a role in the immunoregulation of the tumor microenvironment. Conclusions: CBD has the potential to modulate key molecular processes in CRC through specific pathways and core genes, presenting itself as a possible complementary therapy to improve efficacy and reduce the adverse effects of conventional treatments.